High HIV, hepatitis C and sexual risks among drug-using men who have sex with men in northern Thailand - Chris Beyrer (2018)
Background: Men who have sex with men (MSM) and who use drugs have shown high HIV risks in Europe, and the Americas. We investigated MSM-drug user demographics, HIV sexual and drug use risks and behaviors in Chiang Mai, northern Thailand to identify prevention targets. Methods: A total of 2005 males aged 13 years and older were enrolled during inpatient drug treatment from 1999-2000 and assessed for HIV, hepatitis C virus (HCV), syphilis, and for demographics and risks by questionnaire. Data were analyzed using χ2and multiple logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: Of 2005 males in treatment, 1752 (87.4%) had ever had sex, and 66 of 1752 (3.8%) reported ever having sex with another man; mostly Katoey (transgendered male) partners. MSM had higher HIV rates (OR, 2.32; 95% Cl, 1.36-3.96) and were younger (P = 0.002); more likely to be Thai (P < 0.0001); better educated (P < 0.0001); had more lifetime sex partners (P < 0.0001), more female partners (P = 0.002), more female paid partners (P < 0.0001 ), and been paid for sex (P < 0.0001). MSM were more likely to have ever injected (P < 0.0001), sold drugs, been in prison, injected in prison, used heroin, and to have HCV (OR, 2.59; 95% Cl, 1.55-4.34). Conclusions: Northern Thai MSM-drug users are at high HIV and HCV risk. In addition to sex risks with men, they have more sex with women and sex workers than other men, which fits Thai MSM patterns but not Western ones. Prevention must take into account their high rates of substance use and multiple partner types. © 2005 Lippincott Williams & Wilkins.